Analisis Faktor Keamanan Pada Permodelan Timbunan Yang Diperkuat Geogrid Di Atas Tanah Lempung Lunak - Muzaidi, Irwandy; Anggarini, Elia; Hardiani, Dyah Pradhitya; Sriardi, Doni (AGREGAT, 2024)
The pile built on soft soil has a tendency to fail its submission (bearing failure). This is caused by soft soils to have a low carrying capacity to carry the burden of construction. If a pile must be built which must be completed in a relatively fast time and must be stockpiled on soft soil, can be overcome by reinforcing the soil using geogrid material so as to increase the carrying capacity of soft soil (bearing capacity) and stability of the pile. Analysis uses the element method to the help of plaxis software to find the value of safety, deformation, and voltage changes in the pile built on the soft soil strengthened by geogrid. From this study it was found that the Modeling Piles 2 without Geogrid got a SF 1,0668 value and using Geogrid got a SF 1,3349 value. The safety factor of the pile of land 2 is above 1.25 which means that landslides are rare even without geogrid or use geogrid.